1987
DOI: 10.1002/jlcr.2580241210
|View full text |Cite
|
Sign up to set email alerts
|

Specific deuteration of phenols and aromatic ethers using boron trifluoride and deuterium oxide

Abstract: SUMMARYA number of phenols and aromatic ethers were dcuterated in positions ortho and para to the phenolic groups using BF, etherate followed by quenching with Na,CO, in D,O. This method involves mild reaction conditions and should have wide applicability in the isotopic labeling of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…24 h). It had been reported that the aromatic protons on 3,4,5-trimethoxytoluene were easily exchanged with deuterium under acidic conditions . We also observed the complete disappearance of the aromatic protons on the 3,4,5-trimethoxyphenyl ring when the 1 H NMR spectrum of 1b was measured in CF 3 COOD.…”
Section: Resultssupporting
confidence: 69%
“…24 h). It had been reported that the aromatic protons on 3,4,5-trimethoxytoluene were easily exchanged with deuterium under acidic conditions . We also observed the complete disappearance of the aromatic protons on the 3,4,5-trimethoxyphenyl ring when the 1 H NMR spectrum of 1b was measured in CF 3 COOD.…”
Section: Resultssupporting
confidence: 69%
“…Investigation of the OE in 1,3-bisdiphenylene-2-phenylallyl (BDPA) radicals required the development of synthetic routes that would enable selective 2 H labeling of orthogonal positions on the fluorene moieties, i.e., 1, 3, 6, 8 and 2, 4, 5, 7. Conventionally, the deuteration of aromatic compounds requires harsh reaction conditions, costly catalysts, and/or extended reaction times as aromatic hydrogens are not labile and often lead to poor deuterium incorporation. Efficient direct H/D exchange at alternating positions on arenes is typically achieved by using activating groups, specifically ortho/para directors such as phenols and anilines. …”
Section: Experimental Methodsmentioning
confidence: 99%
“…[2,4- 2 H 2 ]Δ 8 -THC and [2,4- 2 H 2 ]Me-Δ 8 -THC (Figure 1) were synthesized in our laboratory. 21 All 31 P- and 2 H-NMR samples were prepared by the same procedure as described briefly below. [2,4- 2 H 2 ]Δ 8 -THC or [2,4- 2 H 2 ]Me-Δ 8 -THC, DMPC and DHPC were mixed in chloroform (99% pure, Aldrich, Milwaukee, WI), which was then evaporated using an N 2 stream.…”
Section: Methodsmentioning
confidence: 99%
“…1,2-Dimyristoyl- sn -glycero-3-phosphocholine (DMPC) and 1,2-dihexanoyl- sn -glycero-3-phosphocholine (DHPC) were purchased from Avanti Polar Lipids (Alabaster, AL). [2,4- 2 H 2 ]Δ 8 -THC and [2,4- 2 H 2 ]Me-Δ 8 -THC (Figure ) were synthesized in our laboratory . All 13 P and 2 H NMR samples were prepared by the same procedure as described briefly below.…”
Section: Methodsmentioning
confidence: 99%